Perencanaan Karier melalui Workshop Pemetaan Minat, Bakat, dan Tipe Kepribadian Berbasis Myers-Briggs Type Indicator®(MBTI) - Sari, Dian Inda; Rasyid, Mhd. Andi; Rinanda, Teja; Subambang , Subambang H; Sriyanto, Darmawan (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This workshop aims to help students’ carrier planning to their interest in their future major in university by using a worksheet of combination of the Myers-Briggs Type Indicator® (MBTI), the interest and talent approach. This workshop was used PAR (Participatory Action Research) methods in two private vocational schools and one high school in Medan involving 194 students. The results of the worksheet showed that there were differences in several simulation indicators from high school and vocational school students. Another interesting finding was that the majority of students chose their favorite world as introverts. The interest and talent test showed that they were already in the interests and talents that supported their majors. It hoped that the results of this simple test will be an input for students to plan their careers by mapping their interests, talents, and personality types.